Research Methodologies in Urban Wolof Studies: A Critical Review of the Literature and Suggestion for New Analytical Perspectives - Dieng, Aziz (European Scientific Journal, ESJ, 2022)
The aim of this review is to offer a reconceptualization of urban Wolof, the language of millions of Senegalese in Senegal and abroad, in the light of the translanguaging theory. Whereas most of the Urban Wolof literature is principally limited to how this languaging form is spoken in Senegal, the present study considers the effects of mobility on urban Wolof by establishing a correlation between transmigration and translanguaging. Going beyond the confines of Senegal, this investigation examines how the Senegalese diasporans engage in their daily translanguaging practices, as they move across borders, in their capacity as mobile multilingual transmigrants. The review offers a more speaker-centred stance, a sort of bottom-up approach to language, the objective being to move away from the a priori assumptions that the urban Wolophone shuttles between languages or codes, and away from the rigidity of code-based theoretical approaches through which scholars have thus far examined urban Wolof. As such, a more decolonised approach in terms of participatory data collection and analysis is now more than ever in order. And this endeavour should be facilitated by the affordances of the ethnographic gaze of an in-group member.